ADRENAL iNCIDENTALOMA - Ivana Mladenovska Stojkoska; Brankica Krstevska; Irfan Ahmeti; Biljana Todorova (My University, 2014)
Introduction: Adrenal incidentalomas are tumors larger than 1 cm in diameter that is found incidentally by the radiographic imaging of the abdomen and chest(abdominal ultrasonography, CT scanning and MRI).From adrenal incidentaloma 85% are non-functional adrenal masses and the rest 15% are hormonal secreting tumors.From them 9,2 % are presented like subclinical Cushing Syndroma, 4,2 % are Pheochromocytoma and 1.6% are aldosteronoma. Adrenal carcinomas are very rare and 98% are larger than 4 cm in diameter. Aim : During a period of two years in the Clinic of Endocrinology clinical, hormonal and radiographic were evaluated patients with adrenal incidentalomas. Materilas and Methods: We present 20 patients with adrenal incidentalomas evaluated in the Clinic of Endocrinology in therms whether tumor mass is hormonally active and whether it is begin or malignant. Results: From 20 patients with adrenal incidentalomas 15 (75 %) were women and 5 (25 %) were men of average age 48 years. From them 11 (55 %) were detected on the right adrenal gland, 6 (30%) are on the left and 3 (15%) were bilateral. Incidentalomas were with average diametar 2,98 sm. Hormonal test showed that 16 (80 %) are not normonally- secreting tumors and 4 (20%) are hormonslly secreting tumors from witch 1 (5%) presented as malignant pheochromocytoma, 3 (15%) as subclinical Cushing's syndroma. Conclusion: Hormonally active adrenal incidentalomas should be surgically removed. Each adrenal mass greater than or equal to 5 cm should be surgically removed.
Keywords: incidentaloma; incidentally detected; malignant